(untitled) (Global Journal of Management and Business Research, 2015)
Agriculture occupies a prominent position in Indian economy, not only because it accounts for 17 per cent of India’s gross domestic product (GDP) but also engages more than 50 per cent of the country’s workforce. However, Indian Agriculture is confronting the major challenges with respect to ever growing population to feed, reducing natural resources, increasing global competitiveness, deficiency of scientific storage facilities, and above all, uncertainties of the monsoon and changing climate. The small farmers do not have the financial strength to hold the produce with them and are unable to get better off season prices of their agricultural produce. The government buys food grains from the farmers but likewise does not have the space to store it.